2014
DOI: 10.1186/s40152-014-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

How do small-scale fishers adapt to environmental variability? Lessons from Baja California, Sur, Mexico

Abstract: Many fisheries stocks and the livelihoods of those who make their living from fishing are in decline, and these declines are exacerbated by uncertainties associated with increased climate variability and change. Social scientists have long documented the importance of mobility and diversification in reducing the risk and uncertainty associated with climate variability, particularly in the context of small-scale fishing. However, it is unclear how these traditional mechanisms are buffering fishers against the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 46 publications
6
48
1
1
Order By: Relevance
“…Some fishers undertake seasonal migrations and engage in other seasonal work to counteract a loss of income from decreased fish catch (Sievanen, ). Traditional ecological knowledge can help fishers find new fishing areas, switch gear types and take on other jobs (Sievanen, ). Musinguzi et al.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Some fishers undertake seasonal migrations and engage in other seasonal work to counteract a loss of income from decreased fish catch (Sievanen, ). Traditional ecological knowledge can help fishers find new fishing areas, switch gear types and take on other jobs (Sievanen, ). Musinguzi et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some fishers undertake seasonal migrations and engage in other seasonal work to counteract a loss of income from decreased fish catch (Sievanen, 2014). Traditional ecological knowledge can help fishers find new fishing areas, switch gear types and take on other jobs (Sievanen, 2014). Musinguzi et al (2016) reported fishers in Uganda were aware of climate change and its impacts on fish harvests and responded by spending more time fishing, shifting target species and using different types of fishing gears (Musinguzi et al, 2016).…”
Section: Livelihood Adaption Adaptive Capacity and Coping Mechanismsmentioning
confidence: 99%
“…Adaptive strategies that fishers employ include changes in how, when, where, and what to fish (Wilson 2017). Strategies involving changes in fishing activities include changing harvest method (Cinner et al 2015), engaging in seasonal fishing effort (Sievanen 2014), and changing the intensity of fishing activity . Changes to the intensity of harvest may have either dampening or amplifying feedbacks on the exploitation of target species, depending on fishers' socioeconomic characteristics and livelihood options, which influence their responses to change .…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances from natural hazard, climate variabilities as well as economic shocks due to their isolation making them more vulnerable to fall into a poverty trap. Hence, developing alternatives livelihood is the only sensible way to cope with such vulnerability (Allison & Ellis, 2001;Sievanen, 2014). Such a situation is faced by coastal communities of Nembrala village in Rote island, East Nusa Tenggara province.…”
Section: Jurnal Ekonomi Pembangunan 18 (2) 2017 175-182mentioning
confidence: 99%